Outer approximation algorithms to solve semi-infinite environmental pollution problems - Fedossova, Alina; Fedosov, Valery; Buitrago Suescún, Oscar Yecid (Inge Cuc, 2018)
Introduction: The traditional approaches of managing the integral estimation of a general function do no solve the problema of fulfilling the constraints in each point of the domain. This is achieved through a semi-infinite formulation of the problem, in which there are great possibilities in modeling many practical situations of industrial ecology. Some of them are presented in this paper.Objective: Based on detailed studies ([1]-[3]), the aim of this research paper is to examine the mentioned studies in order to contribute to disseminate SIP (Semi-Infinite Programming) applications in environmental pollution control.Methodology: With regard to the numerical solution a stochastic outer approximation algorithm was used, in addition numerical experiments were performed in MATLAB.Results: The obtained results of this work have showed three patterns, the first one enhances the power of emitting pollution sources, taking into account the area landscape, the second one also enhances the power of pollution sources using wind displacement of emissions, finally the third pattern operates by improving the pollution of 3D areas between a group of emission sources and purifiers.Conclusions: In conclusion, it can be said that the issue of power from emitting pollution sources, by considering the area landscape and wind displacement of emissions, should be modeled such as a semi-infinite programming trouble. The method used to calculate the algorithm stopping criterion, does not interpret this solution as an additional problem. Introducción: Los enfoques tradicionales de gestión de la estimación integral de una función general no resuelven el problema de cumplir con las restricciones en cada punto del dominio. Esto se logra mediante una formulación semi-infinita del problema, en la que existen grandes posibilidades para modelar muchas situaciones prácticas de la ecología industrial. Algunos de ellos se presentan en este documento.Objetivo: Basándose en estudios detallados ([1]-[3]) el propósito de este artículo es examinarlos y contribuir a difundir las aplicaciones de la programación semi-infinita (SIP) en la solución de problemas de control de contaminación ambiental.Metodología: Para su solución numérica se aplica el algoritmo estocástico de aproximaciones externas. Los experimentos se realizan en MATLAB.Resultados: Se presentan tres modelos, uno de ellos optimiza la potencia de emisiones de contaminación por fuentes de contaminación teniendo en cuenta el área de ambiente. Segundo, optimiza la potencia de fuentes de polución con sus desplazamientos causado por el viento y el último optimiza la polución en áreas 3D entre un grupo de contaminantes y un grupo de purificadores.Conclusiones: El problema de optimización de emisiones de las fuentes de contaminación teniendo en cuenta el área y sus desplazamientos por causa del viento puede ser modelado y resuelto como un problema de optimización semi-infinita. El criterio de parada del método utilizado no requiere solución de un problema adicional como normalmente sucede en este tipo de programación.